‘If you smoke, you stink.’ Denormalisation strategies for the improvement of health-related behaviours: the case of tobacco - Voigt, K (Springer, 2013)
Denormalisation has emerged as a possible strategy to influence health-related behaviours, particularly in the context of anti-smoking initiatives. Denormalisation strategies aim to influence social norms surrounding the behav-iour in question, by making the behaviour less visible and reducing its social ac-ceptability, so as to motivate individuals to change behaviours and to strengthen public support for other public health measures and interventions. Focusing on anti-smoking efforts, this chapter assesses denormalisation strategies with respect to two concerns. First, denormalisation strategies may contribute to the stigmatisation of smokers. Second, denormalisation strategies may add to existing burdens among disadvantaged groups. These concerns point to highly problematic and potentially counterproductive effects of denormalisation strategies. However, two approaches – social norms marketing and tobacco industry denormalisation – could provide more constructive and less problematic applications of the denormalisation strategy and may therefore have a role to play in the pursuit of public health.